2011
DOI: 10.1007/s00228-011-1193-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 inhibition in cardiac ischemia/reperfusion injury

Abstract: The p38 mitogen-activated protein kinases (p38s) are Ser/Thr kinases that are activated as a result of cellular stresses and various pathological conditions, including myocardial ischemia/reperfusion. p38 activation has been shown to accentuate myocardial injury and impair cardiac function. Inhibition of p38 activation and its activity has been proposed to be cardioprotective by slowing the rate of myocardial damage and improving cardiac function. The growing body of evidence on the use of p38 inhibitors as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 81 publications
1
33
0
3
Order By: Relevance
“…Recently, p38 has been represented as an emerging therapeutic target for the treatment of various conditions, including Alzheimer's disease, cardiac ischemia/reperfusion injury and chronic airways disease. 23,37,38 Thus, further efforts to discover new compounds that can specifically inhibit ASK1-p38 signaling for a prolonged period may lead to the development of novel strategies for the management of deteriorating diseases including retinal and optic nerve degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, p38 has been represented as an emerging therapeutic target for the treatment of various conditions, including Alzheimer's disease, cardiac ischemia/reperfusion injury and chronic airways disease. 23,37,38 Thus, further efforts to discover new compounds that can specifically inhibit ASK1-p38 signaling for a prolonged period may lead to the development of novel strategies for the management of deteriorating diseases including retinal and optic nerve degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the activation of the 38 kDa mitogen which activates protein kinase (p38 MAPK) during myocardial ischemia aggravates lethal cellular injury, particularly during I/R injury (Bogoyevitch et al, 1996;Clark et al, 2007;Kumphune et al, 2012). The pharmacological catalytic site inhibitor SB203580 has been shown to prevent p38 MAPK activation, and has beneficial effects on the heart, including reduced cardiomyocyte death and infarct size as well as attenuation of left ventricular function impairment in the myocardial I/R model (Barancik et al, 2000;Clark et al, 2007;Kumphune et al, 2010;Surinkaew et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ERK1/2-PP1a pathway regulates the expression of phosphorylated PLB and SERCA2a [14]. The p38 MAPK pathway is another important pathway of the MAPK family, and p38 MAPK pathway inhibition could alleviate cardiomyocyte I/R injury and develop cardio-protective effects [15, 16]. In a recent randomized phase 2 trial in non-ST-segment elevation myocardial infarction, Newby et al observed that the use of a novel p38 mitogen-activated protein kinase inhibitor, losmapimod, was well tolerated in non-ST-segment elevation myocardial infarction patients and might improve outcomes after acute coronary syndromes [17].…”
Section: Introductionmentioning
confidence: 99%